EVALUASI PERBANDINGAN PELAKSANAAN KURIKULUM 2013 DAN KTSP PADA PEMBELAJARAN GEOGRAFI DI SMAN KOTA PADANG - Simponi, Maijem; Yanto, Andri; Rahayu, Intan Dwi; Veni, Veni; Putri, Desi Eka; Sari, Tiara Indah; Afrianto, Nanda (STKIP Pesisir Selatan, 2024)
Based on literature studies and researcher observations, the problems encountered in the implementation of the 2013 curriculum are reflected in the difficulty of changing teachers' mindsets, changing the learning process from teacher centered to student centered, low spiritual morals, low reading and research culture, lack of mastery of technology by teachers, weak mastery. in the field of administration, the tendency of teachers to emphasize more on cognitive aspects, there are still many teachers who do not want to become human learners, a teacher is required to continue to increase knowledge and broaden his horizons, especially after the implementation of the 2013 curriculum. These problems make the 2013 curriculum difficult for some schools to accept, including high schools spread across Padang City. Similar to other regions, Padang City also complained about learning based on the 2013 curriculum. One of the subjects affected by this curriculum change was geography. As is the case in high school (SMA), geography learning has been given specifically since the first grade of school, while in grades two and three geography learning is only given to students who choose the Social Sciences major. The KTSP problem can be seen from the lack of creativity of teachers who are trusted as educators.